2023
DOI: 10.1186/s12877-023-03804-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of regional cerebral oxygen saturation monitoring on postoperative cognitive dysfunction in older patients: a systematic review and meta-analysis

Abstract: Background: Postoperative cognitive dysfunction (POCD) is common after surgery and anesthesia, particularly in older patients. It has been reported that regional cerebral oxygen saturation (rSO2) monitoring potentially influences the occurrence of POCD. However, its role in the prevention of POCD remains controversial in older patients. Additionally, the quality of evidence on this topic is still relatively poor. Methods: The electronic databases P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
4
0
1
Order By: Relevance
“…The neurological deficits associated with IJVV incompetence are thought to be caused by cerebral hypoperfusion resulting from increased ICP by brain venous congestion. Cerebrovascular autoregulation plays a significant role in maintaining the stability of blood flow and cerebral perfusion pressure ( 17 , 18 ), but if it is disturbed, arterial hypertension may induce cerebral hyperemia and brain edema, while low arterial blood pressure can lead to cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…The neurological deficits associated with IJVV incompetence are thought to be caused by cerebral hypoperfusion resulting from increased ICP by brain venous congestion. Cerebrovascular autoregulation plays a significant role in maintaining the stability of blood flow and cerebral perfusion pressure ( 17 , 18 ), but if it is disturbed, arterial hypertension may induce cerebral hyperemia and brain edema, while low arterial blood pressure can lead to cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…The use of rScO2 monitoring has been found to be associated with a lower risk of POCD and a shorter length of hospital stay in older patients undergoing noncardiac surgery. It has been suggested that rScO2 monitoring in high-risk populations may have the potential to prevent POCD 23 . In the past, evidence on whether interventions for cerebral oxygen desaturations reduce the risk of neurological outcomes has been limited to case reports and observational studies.…”
Section: Murniece Et Al Examined the Effect Of An Intraoperativementioning
confidence: 99%
“…blisko infracrvena spektroskopija), uređaja koji se koristi za monitoring regionalne cerebralne saturacije, te provođenje intervencijskih algoritama u slučaju cerebralne desaturacije, značajno snižava stupanj, tra janje i učestalost intraoperacijskih cerebralnih desatu racija, kao i nastanak novih lezija mozga utvrđenih MRom, ali bez jasnog dokaza o smanjenu učestalosti POKPa. [38][39][40] S obzirom kako je uporaba KPBa povezana s rizi kom nastanka ishemijskoreperfuzijske ozljede, ugro ženi bolesnici se u kliničkoj praksi intraoperacijski učestalo izlažu visokim koncentracijama kisika kako bi se izbjegla hipoksija mozga i miokarda. U zadnje vrijeme navodi se mogućnost kako je primjena hipe roksije škodljiva za bolesnika zbog pogoršanja ishe mijskoreperfuzijske ozljede i izazivanja izravne ozlje de tkiva reaktivnim spojevima kisika.…”
Section: Patogeneza Pokp-aunclassified